2017
DOI: 10.12659/msmbr.905447
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nicotine and Tocotrienol-Rich Fraction Supplementation on Cytoskeletal Structures of Murine Pre-Implantation Embryos

Abstract: BackgroundCytoskeletal structures, in particular actin and tubulin, provide a fundamental framework in all cells, including embryos. The objective of this study was to evaluate the effects of nicotine, which is a source of oxidative stress, and subsequent supplementation with Tocotrienol-rich fraction (TRF) on actin and tubulin of 2- and 8-cell murine embryos.Material/MethodsThirty female Balb/C mice were divided into 4 groups: Group 1 received: subcutaneous (sc) injection of 0.9% NaCl; Group 2 received sc inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
3
1
0
Order By: Relevance
“…Nic as an OS inducer has been well established in the previous studies [14,27,40,41]. This study has further confirmed the effects of Nic as an OS inducer, as shown in our data on the increase of OS markers level in the Nic group.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Nic as an OS inducer has been well established in the previous studies [14,27,40,41]. This study has further confirmed the effects of Nic as an OS inducer, as shown in our data on the increase of OS markers level in the Nic group.…”
Section: Discussionsupporting
confidence: 91%
“…This data showed the detrimental effects on Nic whereby it these genes which involve in PI3K/Akt pathway may affect the continuity of the cell and nucleus division and may eventually disrupt the development of the preimplantation embryos. We have also documented previously that the actin and tubulin arrangement was also disrupted by Nic in the pre-implantation embryos, which in turn, affecting the embryonic development [41]. Disruption of the cytoskeletal arrangement could be due to the modulation of the PI3K/Akt genes, as shown in this study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Nevertheless, over the years, TRF was documented to exhibit many benefits. In one of the more recent studies, TRF was able to restore actin in cells of murine pre-implantation embryos, after been exposed to oxidative stress triggered by nicotine (Hamirah et al 2017). It also has healing properties; such as protecting astrocytes against glutamate toxicity (Abedi et al 2017), and reducing UV-induced skin redness (Yap 2018).…”
Section: Discussionmentioning
confidence: 98%